Vous êtes sur la page 1sur 4

(FX =0)

FAD + FACh = 0
FAD + (COS 50 X FAC) = 0

FAD = - (COS 50 X -65.27)


FAD = + 41.95

(EFY = 0)
VA + FACV = 0
50 + (Sin 50 x FAC) = 0
Sin 50 X FAC = 50
FAC = -50 = - 65.27
Sin 50

(EFX =0)
FCE + FCDh --- FACh=0
FCE + (COS 50 X FCD)-(COS 50

XFCA)= 0
FCE+ (COS 50 X -65.27)-(COS50 x
-65.27) = 0
FCE = - 41.95 41.25 = -83.9N

(EFY = 0)
-FCDV FACV= 0
-(Sin 50 x FCD)-(SIN50 x FAC) = 0
Sin 50 X FCD =-SIN 50 x FAC
SIN 50 x FCD = 50

FCD = 50 = 65.27
Sin 50

(EFX =0)
FDF+FDE h -FDA-FDC h =0
FDF + (COS 50 X FDE)-FDA-(COS 50
FDC)= 0
FDF+ (-41.95)-41.25-(COS50 x
=0

-65.27)

FDF = 41.95 + 41.95 = 125.85N

(EFY = 0)
FDCV + FDEV = 0
(Sin 50 x FDC)+(SIN50 x FDE) = 0
(Sin 50 X 65.27)+(SIN 50 x FDE)=0
SIN 50 x FDE = -(SIN 50X 65.27)
FDE = -50 = -65.27N
Sin 50

FEG = - 41.95 -83.9-41.95 = 167.8N


FEF = 50 = 65.27N
Sin 50

FGF = -41.95 = - 65.27N


COS 50

FHF = 209.75

(EFY = 0)

FHG = -50 = - 65.27N


Sin 50

FHI V + FHG V = 0

(Sin 50 x FHI) + (Sin 50 x


FHG) = 0
FHG = - (Sin 50 x FHI)
Sin 50

65.27N = 50 = FGH
Sin 50

(EFX = 0)
-

FBJ FBKh = 0
FBJ (COS 50 X FBK) = 0
+ FBJ = - (COS 50 X -65.27) = 0
FBJ + 41.95 N
(EFY = )

VB + FBKV = 0
50 + (Sin 50 x FBK) = 0
Sin 50 X FBK = - 50
FBK = -50 = -65.27N
Sin 50

(EFX = 0)
-FKI FKJ h + FKB h =0
- FKI - (COS 50 X FBJ) + (COS

50 X FBK) = 0
FKI = - (COS 50 X -65.27) + (COS

50 X -65.27)
FKI = -41.95 -41.95=
-83.9N
(EFY =0)
-FKJ V FKB V = 0

- (Sin 50 x FKJ) - (Sin 50 x FKB)


=0
Sin 50 x FKJ= - (Sin 50 x -65.27)

FKJ = -50 = +65.27N


Sin 50

(EFX = 0)
FJB + FJK h FJH FJI h = 0
FJB + (COS 50 X FJK) FJH

(COS 50 X FJI) = 0
FJH = FJB + (COS 50 X FJK) (COS 50 X FJI)
FJH = 41.95 + (41.95) (-41.95)

FJH = +125.8

(EFY = 0)
FJKV + FJIV = 0
(Sin 50 x FJK) - (Sin 50 x FJI) = 0
Sin 50 x FJI= - (Sin 50 x -FJK)

FJI = -50 = +65.27N


Sin 50

(EFX = 0) FIK + FIJh FIG FIHh = 0


FIG = FIK + FIJh - FIJh

FIG = - 83.9 + (COS 50 X FJI) - (COS


50 X FIH)
FIG = - 83.9 + (-41.95) + (-41.95
FIG = - 167.8
N

(EFY = 0)
-FIJ V FIH V = 0
- (Sin 50 x FIJ) - - (Sin 50 x FIH) = 0
- (Sin 50 x -65.27) = SIN 50 X FIH

FIH = -50 =
(65.27N)